2016
DOI: 10.1111/ijcs.12297
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting parents’ choices of functional foods targeted for children

Abstract: In recent years the link between diet and disease has become well established, with studies increasingly pointing to the role of diet in disease prevention, as well as its ability to prevent chronic diseases affecting children. As a consequence, there are ever more functional products specifically targeting children, marketed in terms of the benefits conferred on children's health as well as their potential in reducing the risk of disease. The current study aims to explore factors affecting parents’ choices of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
29
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 51 publications
5
29
0
Order By: Relevance
“…This is similar for functional food in a study by Annunziata et al. (), but different for Vecchio et al. () who showed a higher willingness to pay for functional food. Residence: Living in urban or rural areas also affects consumers’ food technology evaluation that are rather mixed (Canavari & Nayga, ; Olofsson, Öhman, & Rashid, ; Onyango & Nayga, ).…”
Section: Results Of the Reviewsupporting
confidence: 64%
See 3 more Smart Citations
“…This is similar for functional food in a study by Annunziata et al. (), but different for Vecchio et al. () who showed a higher willingness to pay for functional food. Residence: Living in urban or rural areas also affects consumers’ food technology evaluation that are rather mixed (Canavari & Nayga, ; Olofsson, Öhman, & Rashid, ; Onyango & Nayga, ).…”
Section: Results Of the Reviewsupporting
confidence: 64%
“…The specific relationships are explained in more detail in the following paragraphs. Information assessment: There is a tendency for a positive relationship toward evaluation of new food technologies, that is, the more knowledge a consumer has about, or the more familiar a consumer is with the new technology, the better and more positive is the food evaluation (with respect to GM: Amin, Othman, Lip, Jusoff, & Jusoff, ; Baker & Burnham, ; Lusk et al., ; fortification: Annunziata, Vecchio, & Kraus, ; Brečić, Gorton, & Barjolle, ; and nanotechnology: Kim & Kim, ). For example, an experimental auction by La Barbera, Amato, and Sannino () demonstrated the positive effect of level of (subjective) knowledge about lycopene on willingness to pay for functionalized healthy food in both auctions condition (hypothetical compared with real).…”
Section: Results Of the Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…More specifically, a study of Van Wezemael et al (2014) investigates consumer preferences for nutritional and health claims (NHCs) on lean beef steak in four EU countries (Belgium, France, the Netherlands and United Kingdom) found that in Belgium, the Netherlands and France, NHCs on saturated fat yielded higher utilities than claims on protein and/or iron, while the opposite was found among consumers in the UK. On the other hand, studies conducted in different countries covering a broad range of issues including consumers' attitudes and perceptions (Urala & Lahteenmaki, 2007;Masson et al, 2016), preferences (Betchtold & Abdulai, 2014;Annunziata & Vecchio, 2016) and WTP for functional food products with NHCs (Hellyer et al, 2012;Hirogaki, 2013;Cavaliere et al, 2015;de-Magistris & Lopez-Galan, 2016;Jurado & Gracia, 2017;LopezGalan & de-Magistris, 2017) found that healthconscious consumers have positive perception and are willing to pay premium prices for food products with NHCs. Others indicate that healthier perceptions and acceptance of functional foods with NHCs depend on the ingredients and their combination within the product.…”
Section: Introductionmentioning
confidence: 99%